Functional Inequalities for Generalized Complete Elliptic Integrals with Two Parameters. (7th July 2019) - Dou, Xiangkai; Yin, Li; Lin, Xiu-Li
Abstract : In this paper, we establish some functional inequalities for generalized complete elliptic integrals with two parameters, such as estimation of bounds and mean inequalities. Our main results give( p, q ) -analogues to the early results for classical complete elliptic integrals.